Effect of terpenes on transdermal iontophoretic delivery of diclofenac potassium under constant voltage. (14th September 2018) - Arunkumar, S.; Shivakumar, H. N.; Narasimha Murthy, S.
Abstract: Objective: The aim of the study was to enhance the transdermal delivery of diclofenac potassium (DP) from hydrogels by constant voltage iontophoresis (CVI). The other objective was to establish the safety and efficacy of CVI in rats. Materials and methods: Hydrogels of DP were developed using hydroxyethyl cellulose as matrix material and geraniol, l -menthol and thymol as iontophoretic efficiency enhancers (IEE). In vitro permeation of hydrogels under CVI (1.5 V) was performed in Franz diffusion cells across porcine skin. The ability of CVI to deliver therapeutic amount of DP in vivo was assessed in rat paw edema model. Results: CVI significantly ( p  < 0.05) increased the steady state flux of DP compared to the passive. The hydrogels containing geraniol and l- menthol enhanced the iontophoretic flux of DP by ∼4.75 and ∼4.49 fold, respectively compared to passive control. The in vivo studies indicated that CVI in combination with IEE, significantly reduced ( p  < 0.05) area under the curve (AUC) of % inflammation compared to passive treatment. An excellent correlation ( r  = 0.996) was noted between in vitro flux values and AUC of % inflammation. Conclusion: The preclinical studies conclusively demonstrated that CVI in combination with IEE's such as geraniol or l- menthol has the potential to safely deliver therapeutic amounts of DP.